Predictors of time to recovery from postpartum hemorrhage in Debre Markos comprehensive specialized hospital, Northwest, Ethiopia, 2020/21 - Bekalu Kassie; Beker Ahmed; Genet Degu (BMC, 2022)
Abstract Background Postpartum hemorrhage is one of the leading causes of maternal deaths worldwide. Early recovery is a performance indicator and better health outcome of patients with postpartum hemorrhage. Therefore, this study aimed to assess time to recovery from postpartum hemorrhage and its predictors in Debre Markos Comprehensive Specialized Hospital, Ethiopia, 2020. Methods A retrospective follow-up study was conducted among 302 women who were diagnosed with postpartum hemorrhage from January 1, 2016 to December 31, 2020 at Debre Markos Comprehensive Specialized Hospital. Consecutive sampling technique was employed. To show the statistical significant difference between each group of variables, log rank test was used. Kaplan Meier analysis to estimate time to recovery and cox proportional-hazard regression analysis to determine independent predictors were carried out cautiously. Adjusted hazard ratio used to determine the strength of association. Result The median recovery time from postpartum hemorrhage was 13 h with range of (10 to 17 h). Blood transfusion (AHR: 1.8, 95% CI (1.39, 2.57)), NASG utilization (AHR: 6.5, 95% CI (4.58, 9.42)) fluid resuscitation (AHR 2.9, 95% CI (1.48, 5.54)), active management of third stage of labor (AHR: 1.7, 95% CI (1.18, 2.45)) and history of antenatal care follow-up (AHR: 2.6, 95% CI (1.91, 3.56)) were the predictors, which shorten the recovery time. Comorbidities like anemia at the time of admission (AHR: 0.62 95% CI (0.44, 0.89)), retroviral infection (AHR: 0.33, 95% CI (0.16, 0.67)) and Hepatitis B-Virus infection (AHR: 0.52, 95% CI (0.32, 0.82)) delay the recovery rate from postpartum hemorrhage. Conclusion Mothers in North-West Ethiopia stays morbid from postpartum hemorrhage for more than half a day. Their recovery time was affected by Non-Pneumatic Anti-Shock Garment utilization, implementation of emergency management components like blood transfusion and fluid resuscitation, history of antenatal care follow up, and being comorbid with viral infections. Non-pneumatic anti-shock garment application to every mother with postpartum hemorrhage and implementation of proper emergency management approach are vital for rapid recovery from postpartum hemorrhage.